MicroRNA-223 is a novel negative regulator of HSP90B1 in CLL - Rodríguez-Vicente, Ana E (BMC Cancer, 2015)
BACKGROUND: MicroRNAs are known to inhibit gene expression by binding to the 3′UTR of the target transcript. Downregulation of miR-223 has been recently reported to have prognostic significance in CLL. However, there is no evidence of the pathogenetic mechanism of this miRNA in CLL patients. METHODS: By applying next-generation sequencing techniques we have detected a common polymorphism (rs2307842), in 24% of CLL patients, which disrupts the binding site for miR-223 in HSP90B1 3′UTR. We investigated whether miR-223 directly targets HSP90B1 through luciferase assays and ectopic expression of miR-223. Quantitative real-time polymerase chain reaction and western blot were used to determine HSP90B1 expression in CLL patients. The relationship between rs2307842 status, HSP90B1 expression and clinico-biological data were assessed. RESULTS: HSP90B1 is a direct target for miR-223 by interaction with the putative miR-223 binding site. The analysis in paired samples (CD19+ fraction cell and non-CD19+ fraction cell) showed that the presence of rs2307842 and IGHV unmutated genes determined HSP90B1 overexpression in B lymphocytes from CLL patients. These results were confirmed at the protein level by western blot. Of note, HSP90B1 overexpression was independently predictive of shorter time to the first therapy in CLL patients. By contrast, the presence of rs2307842 was not related to the outcome. CONCLUSIONS: HSP90B1 is a direct target gene of miR-223. Our results provide a plausible explanation of why CLL patients harboring miR-223 downregulation are associated with a poor outcome, pointing out HSP90B1 as a new pathogenic mechanism in CLL and a promising therapeutic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1212-2) contains supplementary material, which is available to authorized users.